2018
DOI: 10.5456/wpll.20.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Individual choices? Attitudes to debt and its influence on HE participation decisions

Abstract: This article explores why a group of young people living within traditionally workingclass communities choose not to participate in higher education (HE), even though they have the necessary entry qualifications, and the influence that debt has on their decisions. The research proposes that any strategies devised by the young people were about not owing money and that, at times, the amount of debt appeared to be inconsequential; being in debt was just not the accepted way of doing things. In conjunction with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Although there are a significant number of students enrolling in higher education, it is crucial to remember that persons from largely working-class families are less likely to do so, despite having the necessary entry qualifications and the financial burden of debt (Bailey, 2018). Students' "fear of debt" is linked to their stress levels, implying that more fearful students have experienced more significant stress (Vaicondam & Wen, 2020).…”
Section: Graduated Student Commitmentmentioning
confidence: 99%
“…Although there are a significant number of students enrolling in higher education, it is crucial to remember that persons from largely working-class families are less likely to do so, despite having the necessary entry qualifications and the financial burden of debt (Bailey, 2018). Students' "fear of debt" is linked to their stress levels, implying that more fearful students have experienced more significant stress (Vaicondam & Wen, 2020).…”
Section: Graduated Student Commitmentmentioning
confidence: 99%
“…Research suggests a number of reasons for non-participation in HE including the influence of social class and cultural issues with those young people from relatively disadvantaged areas being shown to be less likely to participate (Callender and Mason, 2017) as well as debt aversion (Esson and Ertl, 2016;Jones, 2016;Bailey, 2018;Evans and Donelly 2019). Other research on the aspirations of non-participants, and how these affect young peoples' desire to participate in HE has shown that some individuals and communities do not see the value of HE participation (Burke, 2012).…”
Section: Influences On Non-participation Decisionsmentioning
confidence: 99%
“…Such decisions seemed rational, they made sense to the participants and they appeared to be influenced significantly by their parents. HE participation was seen as a gamble, and although it may well have led to them gaining more economic capital in the long run, they were not prepared to take a chance (Bailey, 2018). Their future was the world of work.…”
Section: Conclusion: Lessons Learnedmentioning
confidence: 99%